LB3. Daptomycin Plus Fosfomycin vs. Daptomycin Monotherapy for Methicillin-Resistant Staphylococcus aureus Bacteremia: A Multicenter, Randomized, Clinical Trial. (26th November 2018) - Pujol, Miquel; Miro, Jose-Maria; Shaw, Evelyn; Aguado, Jose Maria; Garrido, Rafael San-Juan; Puig, Mireia; Pigrau, Carle; Calbo, Esther; Montejo, Jose Miguel; Rodriguez, Regino; Garcia-Pais, Maria Jose; Pintado, Vicente; et al.
Abstract: Background: Daptomycin plus fosfomycin combination has demonstrated synergistic and bactericidal effect in animal models of methicillin-resistant Staphylococcus aureus bacteremia (MRSAB), but there is lack of data in humans. Method: A randomized (1:1), open-label, clinical trial involving adults with MRSAB was conducted at 18 medical centers in Spain. Patients were assigned to receive daptomycin, 10 mg/kg IV daily plus fosfomycin, 2 g IV/6 hour (combination therapy) or to receive daptomycin 10 mg/kg/24 h IV (monotherapy) during 10 up to 14 days for uncomplicated bacteremia and 28 up to 42 days for complicated bacteremia. The primary efficacy endpoints were: (a) treatment success at Test-of-Cure visit (ToC: 6 weeks after end of therapy) and (b) treatment success at 7 days (defined as alive at day 7 and clearance of bacteremia without relapse from 8 to 90 days after randomization), according with the proposed primary endpoints for use in clinical trials in bloodstream infections in adults. Result: Between December 2013 and November 2017, 674 patients with MRSAB were evaluated and 155 patients were randomized: 74 received combination therapy and 81 monotherapy. In intention-to-treat analysis, (a) at ToC visit successful outcome was achieved in 40 of 74 patients (54, 1%) who received combination therapy as compared with 34 of 81 patients (42%) who were given monotherapy (54.1% vs. 42.0%; absolute difference, 12.1%; 95% confidence interval, 0%-27.0%); (b) at 7 days after starting the therapy: a successful outcome was achieved in 69 of 74 patients who received combination therapy as compared with 62 out of 81 patients who received monotherapy (93.2% vs. 76.5%; absolute difference, 16.7%; 95% confidence interval, 5.4%–27.7%). Combination therapy was associated with lower rates of microbiologic failure than monotherapy at ToC visit (0 vs. 9 patients, P = 0.009). Combination therapy, as compared with daptomycin monotherapy, was associated with a nonsignificantly higher rate of adverse events due to study medication leading to treatment failure and discontinuation of therapy: 6/74 (8.1%) vs. 3/81 (3.7%) ( P = 0.31). Conclusion: The combination of daptomycin plus fosfomycin was more effective than daptomycin alone for treating MRSAB (NCT01898338). Disclosures: All authors: No reported disclosures.